Athletes` jet-lag as a consequence of traveling across six time zones - Vänttinen, T. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume I: Computer Science in Sports., 2008)
Traveling cross time zones causes physiological symptoms better known as jet-lag. Jet-lag is desynchronization of circadian rhythms between the biological time and local time at the country of disembarkation. Previous research has suggested that performance may decline because of jet-lag. The purpose of this study was to examine jet-lag symptoms among athletes crossed six time zones. The subjects of this study were international level wrestlers (n=6, 1,72 ± 0.06 m. 77.1 ± 13.4 kg). Approximately 12 min measurement protocol including budy homeostasis, autonomic nervous system, cognitive functions and performance measurements took place every morning at 7.30 - 8.30 a.m. The results of this study suggest that 4-6 days is needed for athletes to recover from jet-lag. Results also revealed that autonomic nervous system and cognitive functions were first to recover followed by body homeostasis and the performance.